Phosphorus enrichment does not enlarge the predicted CO 2 fertilization effect on forest carbon sequestration - Bin Wang; He Lyu; Xueqian Zhang; Mingkai Jiang; Belinda E. Medlyn; David Wårlind; Jürgen Knauer; Katrin Fleischer; Daniel S. Goll; Stefan Olin; Xiaojuan Yang; Lin Yu; et al. (Proceedings of the National Academy of Sciences, 2026)
The capacity of nutrient-limited forests to enhance carbon (C) sequestration under elevated CO 2 (eCO 2 ) remains a critical uncertainty in C cycle modeling. While existing evidence suggests that low phosphorus (P) bioavailability may constrain CO 2 fertilization effects on plant growth, the extent to which this limitation modulates ecosystem responses to eCO 2 in forests adapted to P-deficient soils remains poorly understood. Here, using eight P-enabled models, we simulated the magnitudes and mechanisms through which P bioavailability interacts with eCO 2 , emulating an ecosystem-scale P enrichment experiment at a P-limited Eucalyptus forest undergoing long-term Free-Air CO 2 Enrichment. While models predicted pronounced P effects on tree growth, P enrichment unexpectedly did not increase the CO 2 effects on tree growth and ecosystem C sequestration. Models prioritized either CO 2 -driven or P-driven growth, but rarely both. This tradeoff emerged due to model-specific assumptions on 1) partitioning of the extra P in soil labile versus nonlabile pools; 2) plant photosynthetic acclimation to P deficiency; 3) C and nutrient use strategies regulating plant size and allocation; and 4) microbial-driven soil decomposition processes. By generating divergent yet biologically plausible outcomes, these predictions establish critical testable hypotheses for empirical research and highlight multiple P-related pathways that may influence the future land C sink.